Comparison of two methods of visual magnification for removal of adhesive flash during bracket placement using two types of orthodontic bonding agents - Estefania Queiroga de Santana e Alencar; Maria de Lourdes Martins Nobrega; Fabio Roberto Dametto; Patrícia Bittencourt Dutra dos Santos; Fabio Henrique de Sá Leitão Pinheiro
ABSTRACT Objective: This study aimed to evaluate the effectiveness of two methods of visual magnification (operating microscope and light head magnifying glass) for removal of composite flash around orthodontic metal brackets. Material and Methods: Brackets were bonded in the center of the clinical crown of sixty well-preserved human premolars. Half of the sample was bonded with conventional Transbond XT (3M Unitek TM, USA), whereas the other half was bonded with Transbond TM Plus Color Change (3M Unitek TM, USA). For each type of composite, the choice of method to remove the flash was determined by randomly distributing the teeth into the following subgroups: A (removal by naked eye, n = 10), B (removal with the aid of light head magnifying glass, under 4x magnification, n = 10), and C (removal with the aid of an operating microscope, under 40x magnification, n = 10). Brackets were debonded and teeth taken to a scanning electron microscope (SS-x-550, Shimadzu, Japan) for visualization of their buccal surface. Quantification of composite flash was performed with Image Pro Plus software, and values were compared by Kruskal-Wallis test and Dunn's post-hoc test at 5% significance level. Results: Removal of pigmented orthodontic adhesive with the aid of light head magnifying glass proved, in general, to be advantageous in comparison to all other methods. Conclusion: There was no advantage in using Transbond TM Plus Color Change alone. Further studies are necessary to draw a more definitive conclusion in regards to the benefits of using an operating microscope.